MODIFYING WORDS IN VOCABULARY BANKS: AN ACTIVE LEARNING STRATEGY TO INCREASE THE STUDENTS’ VERBAL INTELLIGENCE - Hari Wahyono (Universitas Tidar, 2023)
This research aimed to determine the improvement in students’ verbal intelligence resulting from improved the quantity and quality of vocabulary. The study undertook correlation analysis to identify the relationships between research variables, i.e., vocabulary bank and quantity of vocabulary items; the quantity of vocabulary items and quality of vocabulary understanding; quality of vocabulary understanding, and verbal intelligence. The research was undertaken in Madrasah Ibtidaiyah (MI) Al-Islam Balesari, located in Balesari Village, Windusari District, Magelang Regency, Central Java Province, Indonesia. The research sample comprised 50% of all students in the fourth grade and included 9 out of 37 students. The data collection technique in this study was the observation of the correlation between teachers and fourth-grade students at MI Al-Islam Balesari. The data analysis technique used was the Pearson correlation test. The results showed that the vocabulary bank strategy improved students' verbal intelligence. This impacts increased interest and motivation among the students concerning, students' speed in understanding the matters learned, the quality of the reconstruction of aspects studied to be reiterated both written and oral, and improved quantity and quality of students' vocabulary comprehension. Students find it easy to understand the lesson because the information conveyed uses language media that they can understand.